Making Champs and Super-Champs—Current Views, Contradictions, and Future Directions - Collins, David J.; Macnamara, Aine (Frontiers in Psychology, 2017)
In our 2016 paper (Collins et al., 2016a), we proposed that superchamps (athletes who have achieved the highest level in their sport) were differentiated from their less successful counterparts by their use of positive proactive coping and a “learn from it” approach to challenge. This skill-based focus to talent development (TD) is supported extensively in the literature (e.g., MacNamara et al., 2010a, 2010b) and suggests that the differences between levels of adult achievement relate more to what performers bring to the challenges than what they experience (Collins et al., 2016a). In this focused review we present and discuss a number of key concepts related to this paper and other parallel research in TD. We begin by presenting our pragmatic objectives and the importance of considering how we evaluate the research with an emphasis on its application to the applied setting. We then consider commonalities and differences in recent psychological approaches to TD, namely the experiential, attitudinal and skill-based. The paper then provides further exploration of the Psychological Characteristics of Developing Excellence and their role in TD processes. We conclude with a consideration of future research and the application of research in TD. Reflecting our pragmatic stance as researchers, we hope that this focused review provides suggestions for progress and stimulates critical debate amongst practitioners, researchers and policy makers.